Peran Lembaga Keuangan Mikro Syariah dalam Pembiayaan Usaha Mikro Kecil dan Menengah (UMKM) di Kab. Cirebon - Iim Imroah; Mariyah Ulfah; Nur Haida (Fakultas Ekonomi dan Bisni Islam UIN Siber Syekh Nurjati Cirebon, 2025)
BMT is a financial institution that uses sharia patterns. One of its roles in financing the community's economy is by providing capital or financing to customers to help open new businesses or develop existing businesses using Sharia principles to avoid usury. This research aims to determine financing practices, the role of financing for MSMEs and supporting and inhibiting factors for financing at BMT NUS KC Dukupuntang. The method used in this research is a descriptive method, namely research that focuses on solving problems with the aim of describing and explaining the conditions of the research. The data sources obtained are primary and secondary data sources. Primary data sources are information or data obtained directly from the source, interviewing the head of admin and customers. Meanwhile, secondary data sources are data sources obtained from several literatures related to the problem being studied. And data collection techniques are carried out using observation, interviews and documentation. The research results show that the role of sharia microfinance institutions in micro, small and medium enterprises (case study of BMT NUS KC Dukupuntang) states that the practice of murabahah financing is followed by a wakalah (authorization) agreement in procuring goods. The role is quite good in providing financing to customers. Supporting and inhibiting factors in analyzing prospective customers at BMT NUS KC Dukupuntang using the 5C and 7P analysis methods. The factors that support the implementation of financing include material support from members and the existence of adequate facilities and infrastructure.